Candida albicans-epithelial interactions and pathogenicity mechanisms: scratching the surface - Moyes, David L (Virulence, 2015)
Until recently, epithelial cells have been a largely ignored component of host responses to microbes. However, this has been largely overturned over the last decade as an ever increasing number of studies have highlighted the key role that these cells play in many of our interactions with our microbiota and pathogens. Interactions of these cells with Candida albicans have been shown to be critical not just in host responses, but also in fungal cell responses, regulating fungal morphology and gene expression profile. In this review, we will explore the interactions between C. albicans and epithelial cells, and discuss how these interactions affect our relationship with this fungus.